Paramedic Initiated Lisinopril For Acute Stroke Treatment (PIL-FAST): results from the pilot randomised controlled trial. Issue 12 (27th September 2013) - Shaw, Lisa; Price, Christopher; McLure, Sally; Howel, Denise; McColl, Elaine; Younger, Paul; Ford, Gary A
Abstract : Background: High blood pressure (BP) during acute stroke is associated with poorer stroke outcome. Trials of treatments to lower BP have not resulted in improved outcome, but this may be because treatment commenced too late. Emergency medical service staff (paramedics) are uniquely placed to administer early treatment; however, experience of prehospital randomised controlled trials (RCTs) is very limited. Methods: We conducted a pilot RCT to determine the feasibility of a definitive prehospital BP-lowering RCT in acute stroke. Paramedics were trained to identify, consent and deliver a first dose of lisinopril or placebo to adults with suspected stroke and hypertension while responding to the emergency call. Further treatment continued in hospital. Study eligibility, recruitment rate, completeness of receipt of study medication and clinical data (eg, BP) were collected to inform the design of a definitive RCT. Results: In 14 months, 14 participants (median age=73 years, median National Institute of Health Stroke Scale=4) were recruited and received the prehospital dose of medication. Median time from stroke onset (as assessed by paramedic) to treatment was 70 min. Four participants completed 7 days of study treatment. Of ambulance transported suspected stroke patients, 1% were both study eligible and attended by a PIL-FAST paramedic. Conclusions: It is possible to conduct a paramedic initiated double-blind RCT of a treatment for acute stroke. However, to perform a definitive RCT in a reasonable timescale, a large number of trained paramedics across several ambulance services would be needed to recruit the number of patients likely to be required. Clinical trial registration: http://www.clinicaltrials.gov . Unique identifier: NCT01066572 .